Othappu: the scent of the other side - Sarah Joseph (Oxford University Press, 2009)
The third in a trilogy of novels set in Kerala, the book while tracing the personal commitment of a woman to a path that may not lie within the Church, strips away the hypocrisy of organized religion and the great discrimination it practices between the different social classes of Malayali Christians